Implementation of traditional sports development in south sumatra - Susanto, Andreas Guruh; Satria, M. Haris (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Traditional sports in South Sumatra are an important part of the cultural heritage that needs to be preserved. However, their development and practice often receive less attention in modern times. This study highlights the importance of preserving and promoting traditional sports as a means of preserving cultural identity and increasing community participation. This study aims to examine the development and practice of indigenous sports in South Sumatra, and to identify factors that support and inhibit conservation efforts. This study uses qualitative methods with a case study approach. Data was collected through structured interviews with KORMI chairmen, vice chairmen, coaches and athletes. The location of this research is the KORMI SOUTH SUMATRA office. Test the validity of the data in this study was conducted using triangulation techniques by comparing different data sources such as interviews, observations and documentation to ensure the validity, observation and analysis of related documents. Test the validity of the data in this study using triangulation techniques by comparing various data sources such as interviews, observations and documentation to ensure the validity of the findings. The results showed that despite the efforts of various parties to preserve traditional sports, there are still significant challenges such as lack of support from the government and low interest from the younger generation. However, there are local initiatives that are successfully promoting the sport through cultural festivals and educational programmes. This study concludes that in order to maintain the sustainability of traditional sports in South Sumatra, there is a need for synergy between the government, community and educational institutions in promoting and integrating traditional sports into educational and cultural programmes. Further research can be done on the influence of integration and modernisation of traditional culture on the development of athletes in South Sumatra.